Body segments and biological maturation to estimate the propulsive force of the arm in young swimmers - Mariana do Nascimento Sena Oliveira; Daniel da Rocha Queiroz; Marlene Salvina Fernandes da Costa; Arthur Henrique Oliveira da Silva; José Francisco da Silva; Marco Aurélio de Valois Correia Junior; Wilson Viana de Castro Melo; José Cazuza de Farias Junior; Marcos André Moura dos Santos (Universidade Federal de Santa Catarina, 2020)
This study aimed to estimate the propulsive force of the arm (PFA) in young freestyle swimmers and propose an equation to estimate propulsive force, considering anthropometric variables and maturity offset. Seventy-six competitive swimmers [boys: n= 53; age= 13.58 ± 1.79; girls: n= 23; age= 12.98 ± 1.79] participated in this study. Height, lean mass, sitting height, leg length, arm span, triceps skinfold, arm muscle area (AMA), and maturity offset were assessed. The propulsive force of the arm was measured by the tethered swim test. A multiple linear regression (concurrent model) was used to develop the equation using the variables AMA, arm span, and maturity offset. The Bland-Altman method was used to compare the values found between PFA and propulsive force-estimated (PFE). There was a significant correlation between the variables PFA and AMA (R²=0.12; p<0.01), arm span (R²=0.21; p<0.01), and maturity offset (R²=0.20; p<0.01) for boys, whilst in girls theses values were: AMA (R²=0.07;p=0.20), arm span (R²=0.50;p<0.01), and maturity offset (R²=0.44;p<0.01). Two linear equations were established to predict the PFA in boys and girls Bland-Altman analysis showed an agreement between PFA and PFE. In conclusion, the equation is a valuable tool to monitor training and help improve swimmer performance.